Pemberdayaan UMKM melalui Inovasi Pengolahan Pohon Pisang sebagai Alternatif Ketahanan Pangan Berkelanjutan - Catur Prabowo; Ig. Henri Pelupessy; Diva Riza Fahlefi; Rudika Harminingtyas; Maduretno Widowati (Fokus ABDIMAS, 2026)
This community service program aims to empower Micro, Small, and Medium Enterprises (MSMEs) through innovative banana tree processing as an alternative for sustainable food security. While banana trees are currently only utilized for their fruit, they actually have great potential in other parts, such as the heart, stem (pedebog), and roots, to be processed into economically valuable food products. The method used was a participatory approach through training, mentoring, and direct implementation at the Gazray MSME and the Gedung Winong Joint Business Group (KUBE) in Bulusan, Tembalang, Semarang. The results of the activity demonstrated an increase in the knowledge, skills, and product innovation capabilities of MSMEs in processing local raw materials into products such as banana heart-filled spring rolls, banana stem-based fritters, and banana root crackers. Furthermore, this activity also contributed to strengthening local food security and the implementation of the principles of a zero-waste circular economy.